2019
DOI: 10.1051/e3sconf/201913101113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Cold Resistance Physiology of Red Pulp Pitaya and White Pulp Pitaya

Abstract: The red pulp pitaya variety ’Taiwan No. 2’ and the white pulp pitaya variety ’white crystal’ were used as experimental materials, which were cold stressed at low temperature of 3 °C for 48h, 96h, and recovering at room temperature after 96h cold stress for control. The relative conductivity (REC), malondialdehyde content (MDA), soluble sugar content (SS), soluble protein content (SP), free proline content (Pro), activity of superoxide dismutase (SOD), and catalase (CAT) were determined and the cold resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Pitaya thrives at 18–27 °C, but an extreme temperature of 39 °C is not suitable [ 128 ]. Cold damage is the biggest issue in northern China [ 129 , 130 ], while a humid climate causes pests and diseases in pitaya produced in Malaysia [ 131 , 132 ]. A study reported that fresh-cut pitaya fruit storage at 5–10 °C increased the accumulation of total soluble phenolics reactive oxygen species and improved antioxidant activity [ 133 , 134 ].…”
Section: Agronomy Cultivation Pests and Diseasesmentioning
confidence: 99%
“…Pitaya thrives at 18–27 °C, but an extreme temperature of 39 °C is not suitable [ 128 ]. Cold damage is the biggest issue in northern China [ 129 , 130 ], while a humid climate causes pests and diseases in pitaya produced in Malaysia [ 131 , 132 ]. A study reported that fresh-cut pitaya fruit storage at 5–10 °C increased the accumulation of total soluble phenolics reactive oxygen species and improved antioxidant activity [ 133 , 134 ].…”
Section: Agronomy Cultivation Pests and Diseasesmentioning
confidence: 99%
“…A pitaya ou pitaia (gênero Hylocereus), é um fruto exótico apreciado por seus atributos sensoriais e valor nutricional (Covino et al, 2015;Gong et al, 2019;Magalhães et al, 2019). A pitaya é rica em flavonoides e fonte de minerais e vitaminas (C e complexo B), além de possuir elevados teores de fibra, nitrogênio, potássio, cálcio, ferro, manganês e zinco (Cordeiro et al, 2015).…”
Section: Introductionunclassified